Extreme Drought Affects Visitation and Seed Set in a Plant Species in the Central Chilean Andes Heavily Dependent on Hummingbird Pollination - Mary T. K. Arroyo; Valeria Robles; Ítalo Tamburrino; Jaime Martínez-Harms; René D. Garreaud; Paola Jara-Arancio; Patricio Pliscoff; Ana Copier; Jonás Arenas; Joaquín Keymer; Kiara Castro (Plants, 2020)
Rising temperatures and increasing drought in Mediterranean-type climate areas are expected to affect plant–pollinator interactions, especially in plant species with specialised pollination. Central Chile experienced a mega drought between 2010 and 2020 which reached an extreme in the austral summer of 2019–2020. Based on intensive pollinator sampling and floral studies we show that the subalpine form of Mutisia subulata (Asteraceae) is a specialised hummingbird-pollinated species. In a two-year study which included the severest drought year, we quantified visitation frequency, flower-head density, flower-head visitation rates, two measures of floral longevity, nectar characteristics and seed set and monitored climatic variables to detect direct and indirect climate-related effects on pollinator visitation. Flower-head density, nectar standing crop and seed set were significantly reduced in the severest drought year while nectar concentration increased. The best model to explain visitation frequency included flower-head density, relative humidity, temperature, and nectar standing crop with highly significant effects of the first three variables. Results for flower-head density suggest hummingbirds were able to associate visual signals with reduced resource availability and/or were less abundant. The negative effect of lower relative humidity suggests the birds were able to perceive differences in nectar concentration. Reduced seed set per flower-head together with the availability of far fewer ovules in the 2019–2020 austral summer would have resulted in a major reduction in seed set. Longer and more intense droughts in this century could threaten local population persistence in M. subulata.